Public awareness on earthquake and tsunami survey in Penang - Lau, Tze Liang; Taksiah, A. Majid, Assoc. Prof. Dr.; Choong, Kok Keong, Dr.; Shaharuddin Shah, Zaini (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/